Pelaksanaan Giat Sayang Warga Sebagai Wujud Pengabdian Kepada Masyarakat Di Kelurahan Benowo, Kota Surabaya - Zildjianisa Rhisma Widyatna; Tukiman Tukiman (Jurnal Kabar Masyarakat, 2023)
The Surabaya City Population and Civil Registry Office partners with the Ministry of Education, Culture, Research and Technology in the MSIB Batch 4 program. This activity is designed for students who want to assist the Surabaya City Government in providing Population Administration services at the Population and Civil Registration Service, by going directly as a form of service to public. The Sayang Warga service activity program is an innovation by the Surabaya City government which aims to make it easier for the community to manage population administration in a transparent, efficient and effective manner and provide an understanding for the community that orderly population administration is very important for the continuation of a state life. This program runs with the help of village officials who carry out services at the RW hall. The active implementation of this compassionate service for residents has a goal, namely to create an orderly population administration society. Through the MSIB program, the author as an apprentice student hopes to help the Surabaya city government in improving the quality of public services by participating in the Dear Citizens service program in Benowo Village.